African swine fever virus attachment protein. - Carrascosa, A L (1991)
Treatment of African swine fever virus particles with nonionic detergents released proteins p35, p17, p14, and p12 from the virion. Of these proteins, only p12 bound to virus-sensitive Vero cells but not to virus-resistant L or IBRS2 cells. The binding of p12 was abolished by whole African swine fever virus and not by similar concentrations of subviral particles that lacked the external proteins. A monoclonal antibody (24BB7) specific for p12 precipitated a protein that, when analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis in the absence of 2-mercaptoethanol, showed a molecular mass of 17 kDa (p17*) instead of 12 kDa as found in the presence of 2-mercaptoethanol. The relationship between these two proteins was confirmed by the conversion of p17* to p12 when the former was isolated from polyacrylamide gels in the absence of 2-mercaptoethanol and subsequently treated with the reducing agent. The supernatant obtained after immunoprecipitation with the p12-specific antibody lacked the virus-binding protein.